Developing a rule-based method for identifying researchers on Twitter: The case of vaccine discussions - Ekström, Björn (University of Borås, 2019)
This study seeks to develop a method for identifying the occurrences and proportions of researchers, media and other professionals active in Twitter discussions. As a case example, an anonymised dataset from Twitter vaccine discussions is used. The study proposes a method of using keywords as strings within lists to identify classes from user biographies. This provides a way to apply multiple classification principles to a set of Twitter biographies using semantic rules through the Python programming language. The script used for the study is here deposited.

Method development for Twitter biography classification concerning occurrences of academics, academically related groups and individuals, media, other groups and members of the general public. Written in the Python programming language.

Denna studie söker utveckla en metod för att identifiera förekomster och proportioner av forskare, media- och andra professionella aktiva i Twitterdiskussioner. Som ett fallexempel används ett anonymiserat dataset från vaccindiskussioner på Twitter. Studien föreslår en metod som använder nyckelord som strängar inom listor för att identifiera klasser ifrån användarbiografier. Detta möjliggör en applicering av multipla klassifikationsprinciper till en mängd Twitterbiografier genom att använda semantiska regler genom programmeringsspråket Python. Det skript som använts för att genomföra studien är här deponerat.

Metodutveckling för klassning av Twitterbiografier rörande förekomster av akademiker, grupper och individer relaterade till akademi, media, andra grupper samt allmänhet. Skriven i programmeringsspråket Python.
Developing a rule-based method for identifying researchers on Twitter: The case of vaccine discussions
Keywords: classification; klassifikation; social media; sociala media; Higher and further education; Gymnasial och högre utbildning; Information society; Informationssamhället; Language and linguistics; Språk och lingvistik; Natural Language Processing; Språkbehandling och datorlingvistik; Social Sciences; Samhällsvetenskap; Information Studies; Biblioteks- och informationsvetenskap